Intelligent Authentication and Indoor Mobile Navigation System for Visually Disabled - Anusha K, Nachiyappan S, Pradeep K V (International Journal of Advanced Science and Technology, 2020)
Navigation is a fundamental part of our day to day life. It is difficult for normal people to find different locations on their own and for visually impaired people it becomes more difficult. The environment around us is well known by the normal people but, visually disabled or partially abled people are not used to with the environment around them. And a more challenging task for these people will be navigating independently in new space, buildings or environments. The areas and environments around us are marked with signs, boards, and signals that can be viewed by a normal person. The proposed system shows us a way to make visually challenged people roam in the spaces around them without any external guidance or boards. In this paper, a system is proposed. It is an intelligent authentication and navigation system to help visually challenged people to navigate within any environment (e.g. shopping centers, public parks, office buildings). Based on an android application developed exclusively for visually challenged people and using wireless Bluetooth sensors deployed in the environment according to their respective range and locations. The proposed system is an information tracking system that will be able to guide visually challenged people in real-time to their destination and allow them to have all the information about the location. This system offers authentication, navigation through audio commands and provides detailed information about places, locality, and services that are available in the environment around the user. This initiative will change the way of day to day indoor navigation of visually challenged people.